Pengaruh Tangkai Buah terhadap Mutu Fisiologi Cabai Merah Keriting (Capsicum annum L.) - Kristri Yoga; Tamrin Tamrin; Warji Warji; Sapto Kuncoro (abe.fp.unila.ac.id, 2022)
Curly red chili (Capsicum annuum L.) is a horticultural plant that is widely used for food needs. Its use in the industry makes chili as a commodity of high economic value. In general, one of the problems in post-harvest handling of chili is its relatively short shelf life. The aim of the research was to study the effect of stalks on the quality of cayenne pepper during storage. The studies that only used two treatments, namely without stems and with stalks, the study was added to the harvest treatment with the addition of stems from 1 cm stems. This study used a completely randomized design (CRD). This storage uses room temperature with a storage period of 12 days. Each factor and treatment was repeated 3 times so that 9 experimental units were obtained. Parameters observed in this study were weight loss, hardness, moisture content, color, and organoleptic tests. The results showed that the effect of cutting chili stalks at harvest had a significant effect on the moisture content of the material, while weight loss and hardness had no effect. The RGB values of the three treatments showed a continuous decrease for the green color index (Green) and for the red index (Red) showed an increase until the 4th day and decreased until the 12th day. The organoleptic test showed that the texture and freshness parameters had a significant effect on the organoleptic test. Keywords: Add 1 cm Stem, Curly Red Chili, With Stem, Without Stem.